THE ROLE OF BUSINESS MODELS AND MANAGEMENT CONTROL SYSTEMS IN FORVIS MAZARS GROUP’S SUCCESS - Alexandra, Putri; Anandya, Dudi; Setyawan, Andhy (FEB Universitas Sam Ratulangi Manado, 2024)
This study investigates the sustained success of Forvis Mazars Group, a global professional services firm, through the lens of the Business Model Canvas (BMC) framework to analyze its business model. The primary aim is to examine how Mazars' Management Control System (MCS) aligns operational performance with strategic objectives, contributing to the firm's competitive advantage. The journal also explores Forvis Mazars' organizational structure, providing insights into how it facilitates effective communication, collaboration, and decision-making within the firm. Employing a qualitative research approach, the study utilizes a case study method to analyze Forvis Mazars' business model, with data collected from secondary sources that focus on the firm's key activities, resources, partnerships, and control systems to provide a comprehensive overview of its operations. The findings reveal that Forvis Mazars effectively integrates strategic management, operational excellence, and robust control mechanisms to achieve sustained success, highlighting the pivotal role of its MCS in aligning operations with long-term strategic goals while fostering strong client relationships in a highly regulated market. This study offers new insights into Forvis Mazars' approach to business model innovation and organizational growth, serving as a valuable reference for understanding resilience and success in the professional services sector. By applying the BMC framework in this context, the research presents an original perspective on strategic management and control within global markets. Keywords: Business Model Canvas, Management Control System, Organizational Structure